Perspectivas assistenciais de saúde no envelhecimento da população lgbtqiapn+ na atenção primária à saúde - Rodrigues, Romário Gomes (2024)
During the aging of LGBTQIAPN+ people (Lesbians, Gays, Bisexuals, Transvestites, Transsexuals, Transgenders, Queer, Intersex, Asexuals, Pansexuals and Nonbinary) the restriction of access to health care may increase, further impacting the quality of assistance, mainly at the level of Primary Health Care. This study aims to understand the care practices implemented in Primary Health Care for the care of the LGBTQIAPN+ elderly population. Based on a bibliographical investigation that included scoping review research articles and experience reports, an e-book was prepared with the information extracted from this survey. The scoping review had a protocol registered with the OSF (10.17605/OSF. IO/WU3GV), followed the Joanna Briggs Institute (JBI) manual and the PRISMA Extension for Scoping Reviews tool. The bibliographic survey took place in April and May 2023, in databases such as PubMed, LILACS, SciELO and EMBASE, without restrictions on date or study design. In the scope review, it was detected that care for LGBTQIAPN+ aging in Primary Care is made up of numerous challenges, including: insufficient professional training, non-inclusive environments, social isolation, discrimination and barriers to access to healthcare. The experience report highlights the adversities faced when carrying out research on the LGBTQIAPN+ theme, highlighting the need to promote investigations relevant to the health of this community. Furthermore, it highlights the unprecedented nature of this type of research in postgraduate studies at the Federal University of Paraíba (UFPB). The e-book, aimed at managers and health professionals in Primary Care and LGBTQIAPN+ elderly people, disseminates information about LGBTQIAPN+ aging in primary health care. It is concluded that the research can serve as a theoretical and reflective basis for proposing changes and redirecting actions that reinforce care in LGBTQIAPN+ old age. This master's degree work is the result of the Stricto Sensu Professional Master's Postgraduate Program in Family Health (PROFSAÚDE).